Morphologic Damage of Rat Alveolar Epithelial Type II Cells Induced by Bile Acids Could Be Ameliorated by Farnesoid X Receptor Inhibitor Z-Guggulsterone In Vitro. (1st June 2016) - Wang, Jieqin; Huang, Yaowei; Hou, Xusheng; Wu, Wenyu; Nie, Lei; Tian, Yinghong; Lu, Yanmeng; Yin, Yanru
Abstract : Objective . To determine whether bile acids (BAs) affect respiratory functions through the farnesoid X receptor (FXR) expressed in the lungs and to explore the possible mechanisms of BAs-induced respiratory disorder. Methods . Primary cultured alveolar epithelial type II cells (AECIIs) of rat were treated with different concentrations of chenodeoxycholic acid (CDCA) in the presence or absence of FXR inhibitor Z-guggulsterone (GS). Then, expression of FXR in nuclei of AECIIs was assessed by immunofluorescence microscopy. And ultrastructural changes of the cells were observed under transmission electron microscope and analyzed by Image-Pro Plus software. Results . Morphologic damage of AECIIs was exhibited in high BAs group in vitro, with high-level expression of FXR, while FXR inhibitor GS could attenuate the cytotoxicity of BAs to AECIIs. Conclusions . FXR expression was related to the morphologic damage of AECIIs induced by BAs, thus influencing respiratory functions.